Development of an automatic tracking system to determine field efficiency of agricultural machines - Natussapol Tamrai; Boripun Masarn; Apidul Kaewkabthong; Ravipat Lapcharoensuk; Songvoot Sangchan; Vasu Udompetaikul (My University, 2018)
Field efficiency of machines tells how efficient the farm machines are operating in the field. Measuring of the field efficiency used to be a tedious and laborious work which is not worth to collect for further operational optimization. The objective of this study was to develop an automatic system for monitoring the field activities and then evaluation of the field efficiency of farm machines. The system consisted of a microcontroller to collect working data including position, speed heading, and working status of the machine. The system was installed on a farm tractor with plowing disc to test on two fields with the same size, but in different traveling directions, i.e., lengthwise and crosswise. The results showed lengthwise operation yielded a higher field efficiency due to less number of turning at headlands. The proposed system allowed to collect necessary information for detailed efficiency evaluation of farm machines. This technique enables further utilization of the operational information and benefit to use in the optimization of the farm works.
Keywords: Tractor; Agricultural machinery; Combine harvester; Soil Mechanics and Vehicle Dynamics